Handbook on colleges and universities. (Quezon City Fellowship of Christians in Government, 2003)
A compilation of 100 government and private colleges and universities in the Philippines to help students and their families choose a suitable source for tertiary education. Special sections for specialized colleges and scholarship programs are also included.
A comprehensive reference on colleges and universities in the Philippines. The handbook lists the schools into private and state colleges and universities, and specialized colleges. Each school is presented in a profile containing the following information: vision, mission, addresses, contact numbers, courses offered, admission requirements, range of fees and scholarship grants. The handbook also includes a table of CHED Student Financial Assistance Programs showing these programs' legal basis, programs, clientele, and areas of specialization, entry requirements, documentary requirements, application procedures, and financial benefits. It also includes a listing of scholarship programs by other companies and institutions with the following information given:contact information, objectives, criteria of eligibility, documentary requirements, and application procedures, selection of scholars, Scholarship privileges, obligations, and courses offered.
Keywords: Universities and colleges -- Philippines -- Manila Metropolitan Area -- Handbooks, manuals, etc; State colleges and universities -- Philippines -- Manila Metropolitan Area -- Directories; Scholarships -- Philippines -- Manila Metropolitan Area